2014
DOI: 10.2139/ssrn.2448144
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Ability, Character Skills, and Learning to Play Equilibrium: A Level-k Analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 87 publications
7
120
0
Order By: Relevance
“…These measures have 19 In a non-strategic setting, Burks et al (2009) report a correlation of approximately 0.22 between IQ and switching more than once in Holt and Laury's (2002) multiple price list experiments. In a strategic setting, Gill and Prowse (2014) investigate the correlation between cognitive ability and non-cognitive skills and learning to play equilibrium in a repeated p-beauty contest experiment. They estimate a structural model based on level-k reasoning (Stahl and Wilson, 1995;Nagel, 1995;Duffy and Nagel, 1997), and find a systematic relationship between subjects' cognitive ability and their level-k types.…”
Section: Expected-utility Maximizationmentioning
confidence: 99%
“…These measures have 19 In a non-strategic setting, Burks et al (2009) report a correlation of approximately 0.22 between IQ and switching more than once in Holt and Laury's (2002) multiple price list experiments. In a strategic setting, Gill and Prowse (2014) investigate the correlation between cognitive ability and non-cognitive skills and learning to play equilibrium in a repeated p-beauty contest experiment. They estimate a structural model based on level-k reasoning (Stahl and Wilson, 1995;Nagel, 1995;Duffy and Nagel, 1997), and find a systematic relationship between subjects' cognitive ability and their level-k types.…”
Section: Expected-utility Maximizationmentioning
confidence: 99%
“…Carpenter, Graham, and Wolf (2013) showed that subjects with higher scores in Raven's test more frequently win in Race to 5, 10, or 15 games 5 and guessed others' choices better in a 20-player beauty contest game. Finally, Gill and Prowse (2015) also reported that subjects with higher scores in Raven's test not only choose numbers closer to the equilibrium in a repeated 3-player beauty contest game, but also respond to the average score of other subjects in the group by choosing number close to the equilibrium when facing with others with higher scores than when facing with others with lower scores. Fehr and Huck (2015) reported similar results from a beauty contest game.…”
mentioning
confidence: 91%
“…18 The responses to the CRT are indeed a good proxy for the individuals' tendency to make impulsive versus reflective decisions. The CRT has been found to correlate with one's ability to delay gratification (Frederick, 2005) and to predict one's ability to refrain from using inaccurate heuristics in a variety of situations (Oechssler et al, 2009, Toplak et al, 2011 figuring out the equilibrium play in other games (Gill and Prowse, 2016). To test this hypothesis, we elicited a different measure of participants' cognitive ability to solve math problems.…”
mentioning
confidence: 98%